E-learning during COVID-19 Lockdown among College Students of Nepal: Opportunities and Challenges - Pokhrel, Poonam (KMC Journal, 2023)
COVID-19 pandemic had affected all sectors of human life around the globe. Education is one of them where traditional method of teaching had to shift to virtual learning all of sudden in both developed and developing countries. Therefore, the study reflects the opportunities and challenges of e-learning among college students of Nepal during emergency shift of teaching paradigm due to COVID-19 lockdown. Cross-sectional quantitative study with random sampling method using online questionnaire was used to collect 385 data from college students of Nepal during COVID-19 pandemic lockdown. The study showed that 85% of the students had engaged in e-learning during COVID-19 pandemic lockdown whereas only 30% of the students had all the required resources for e-learning. The study further found that 70% respondents had developed new skills and could manage time for study despite lockdown. However, more than half of the students had challenging situations to access the Internet surfing for e-learning followed by management of electronic devices and interaction with teachers by nearly 33%. Educational institutions need to be responsive towards the challenges faced by students during e-learning, so that learning needs of the students will be fulfilled even in crisis situation.